(untitled) (Tikrit Journal of Pharmaceutical Sciences, 2023)
In this research chemical compositions (calcium, magnesium, and inorganic phosphorus ions) of kidney stones using quantitative methods were determined. Forty three calculi [14 from female (32.6%) and 29 of male (67.4%)] were investigated using visible spectrophotometry at different wavelengths. The analytical quantitative methods used for determination the concentrations of these metals were accurate, reliable and sensitive with linear range of (5-65), (0.05-0.5), and (1.5-13.5) μg/ml and standard deviation 0.004596, 0.002390, and 0.000756 and low detection limit (L.O.D.) was 0.1120, 0.0177, and 0.1890 μg/ml while the (RSD) was 1.40%, 2.36%, and 5.04% respectively.The most found kidney stones were either rigid or soft with different shapes and colures. The stones were digested with three solutions [1N HNO3, 16.5N HNO3, and de-ionized water (D.I.W)], the highest concentrations of the Ca, Mg, and P were found at 16.5N HNO3 digest solution.